Correlation between Serum Ferritin Levels and Liver Stiffness measured by Fibroscan in patients with Chronic Hepatitis C - Latif, Saba (Pak J Med Sci, 2020)
OBJECTIVE: To determine correlation between transient elastography values with serum ferritin and duration of infection in patients of hepatitis C. METHODS: A cross-sectional study was conducted at medical units of Civil Hospital, Karachi. The study protocol was approved by the Research Evaluation Unit of College of Physician and Surgeon Pakistan (CPSP). Patients fulfilling inclusion criteria were included after taking informed consent. Serum ferritin levels were tested by standard laboratory procedures and transient elastography by fibroscan. Regression analysis was done to see correlation of ferritin with transient elastography and duration of HCV. RESULTS: Over all 120 patients fulfilling the selection criteria were selected after informed consent. These included 68 (56.7%) male & 52 (43.3%) female. Significant differences in ferritin levels by Fibrosis stages were observed by ANOVA (df = 3; F =12.768; p = <0.001). Serum ferritin showed linear pattern across Fibrosis stages (F = 33.948; p = <0.001). Regression analysis of ferritin and duration of HCV showed significant impact on TE scores (r(2) = 0.317). CONCLUSIONS: There is significant correlation between serum ferritin and duration of HCV with TE scores.